The Dilemma of Parate Executie: Secured Creditors versus Curators in Bankruptcy - Luhut Sagala; Budi Santoso; Ery Agus Priyono (Faculty of Law, University of Merdeka Malang, 2026)
This article analyses the normative conflict between Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (Act on PKPU) and Indonesian collateral law governing execution rights of secured (separatist) creditors. Using a doctrinal method combined with statutory, case, and comparative approaches, the study examines how Articles 56 and 59 of the Act on PKPU restrict parate executie as guaranteed by the Civil Code, the Mortgage Law, and the Fiduciary Law. Findings, corroborated by Supreme Court Decisions No. 158 K/Pdt.Sus/2011 and No. 895 K/Pdt.Sus-Pailit/2016, show that once collateral is surrendered to a curator, recovery for secured creditors is severely eroded by bankruptcy costs and curator fees; in the first case, recovery fell from a claim of Rp44.7 billion to a distribution of only Rp1.5 billion, roughly 3.4 per cent. A comparative reading of United States Chapter 11 and the Dutch Faillissementswet shows Indonesia’s rigid two-month limit is an outlier among comparable regimes. Building on Posner’s economic analysis of law and Rawls’ theory of justice, the article argues the current arrangement is economically inefficient and distributively unjust, and proposes extending the execution window and ring-fencing collateral proceeds to restore secured creditors’ priority while preserving bankruptcy’s collective character and financial stability.